Transceiver Designs for MIMO Relay Communication Systems - Lee, Justine Bing (Curtin University, 2021)
Recently, the application of SWIPT in the energy-limited wireless system has attracted much attention from researchers due to the SWIPT technology provide the capability to prolong the limited lifetime of the wireless system. For a wireless communication system, a relay node helps to extend the network coverage, while the MIMO relay technique helps in enhancing the system performance. In this thesis, the investigation concerning the application of SWIPT in the MIMO relay system is investigated.